153k views
2 votes
WILL MARK BRIANLIEST!

Solve the system of equations using the elimination method.
​Show ALL work

​ x+y=2
x−y=6

1 Answer

5 votes

Answer:

(4, - 2 )

Explanation:

Given the 2 equations

x + y = 2 → (1)

x - y = 6 → (2)

Adding the 2 equations term by term will eliminate the term in y, that is

(x + x) + (y - y) = (2 + 6)

2x = 8 ( divide both sides by 2 )

x = 4

Substitute x = 4 in either of the 2 equations and solve for y

Substituting in (1)

4 + y = 2 ( subtract 4 from both sides )

y = - 2

Solution is (4, - 2 )

User Achyut Rastogi
by
4.9k points